Air Pollution Control Technology Handbook - Schnelle, Karl B. (CRC Press, 2009)
In the debate over pollution control, the price of pollution is a key issue. But which is more costly: clean up or prevention? From regulations to technology selection to equipment design, Air Pollution Control Technology Handbook serves as a single source of information on commonly used air pollution control technology.